1998
DOI: 10.1002/ana.410440605
|View full text |Cite
|
Sign up to set email alerts
|

Matrilineal inheritance of complex I dysfunction in a multigenerational Parkinson's disease family

Abstract: Recent data suggesting complex I dysfunction in Parkinson's disease (PD) arises from mitochondrial DNA (mtDNA) mutation does not conclusively answer whether the responsible genetic lesion is inherited (primary) or somatic (secondary). To address this question, we identified a family in which multiple members over three generations are affected with PD through exclusively maternal lines. Cytoplasmic hybrids (cybrids) were created for 15 family members over two generations by transferring each individual's mtDNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 136 publications
(84 citation statements)
references
References 29 publications
2
80
0
1
Order By: Relevance
“…Decrease in complex I activity in PD brain is in agreement with other reports that showed 30 and 39% reductions in complex I and complex I/III activities, respectively, in the substantia nigra (42) and 32% reduction in the cortex of PD patients (32). Besides these, several groups have also emphasized the importance of impaired mitochondrial complex I activity as the cause of mitochondrial dysfunction in PD models (4,43,44). Another line of direct evidence for the involvement of decreased complex I activity in the pathogenesis of PD comes from studies administering complex I inhibitors such as rotenone and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine to rodents, which showed mitochondrial dysfunction as well as the loss of dopaminergic neurons (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…Decrease in complex I activity in PD brain is in agreement with other reports that showed 30 and 39% reductions in complex I and complex I/III activities, respectively, in the substantia nigra (42) and 32% reduction in the cortex of PD patients (32). Besides these, several groups have also emphasized the importance of impaired mitochondrial complex I activity as the cause of mitochondrial dysfunction in PD models (4,43,44). Another line of direct evidence for the involvement of decreased complex I activity in the pathogenesis of PD comes from studies administering complex I inhibitors such as rotenone and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine to rodents, which showed mitochondrial dysfunction as well as the loss of dopaminergic neurons (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dysfunction in sporadic PD appears to arise at least in part from mtDNA (Swerdlow et al, 1996(Swerdlow et al, , 1998Gu et al, 1998;Shults and Miller, 1998). Interestingly, relative to other brain areas the substantia nigra contains particularly high levels of large mtDNA deletions (Soong et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…This approach has previously been used to produce cell culture models of PD mitochondrial dysfunction; successful studies utilizing SH-SY5Y and A549 human cell line nuclear backgrounds are reported (Swerdlow et al, 1996(Swerdlow et al, , 1998Gu et al, 1998;Shults and Miller, 1998). This technique involves the transfer of platelet mitochondria from either PD or control subjects to mtDNAdepleted recipient cells (rho0 cells).…”
Section: Introductionmentioning
confidence: 99%
“…Shults and Miller reported the results of their SH-SY5Y cybrid study in 1998 (120). Also in 1998, Swerdlow et al prepared SH-SY5Y cybrid cell lines from members of an extended family in which PD appeared to pass through maternal lines of inheritance (137). In that study, cybrid cell lines prepared using platelet mitochondria from PD-affected kindred members and the young, asymptomatic descendents of PD mothers had lower complex I activities than cybrid cell lines prepared from platelet mitochondria obtained from asymptomatic kindred members descended through paternal lines.…”
Section: Swerdlow Complex I Activity Is Reduced In Pd Cybridsmentioning
confidence: 92%
“…PD cybrid mitochondrial ultrastructure is altered (34,137,148). Mitochondria tend to be larger and are more likely to show disruption of cristae than mitochondria in control cybrids.…”
Section: Pd Cybrid Modeling Of Other Pd-associated Pathologiesmentioning
confidence: 99%